PENGARUH KEDISIPLINAN SISWA SAAT PEMBELAJARAN JARAK JAUH TERHADAP HASIL BELAJAR SISWA KELAS V SEKOLAH DASAR - Siti Maryam, - (2021)
Penelitian ini dilatarbelakangi oleh masalah yang dihadapi saat Pembelajaran jarak jauh (PJJ) yang terjadi salah satunya pada pribadi siswa sendiri yang kurang disiplin. Adapun tujuan penelitian ini yaitu: 1) Untuk mengetahui kedisiplinan siswa kelas V sekolah dasar saat PJJ, 2) Untuk mengetahui hasil belajar siswa kelas V sekolah dasar, 3) Untuk mengetahui apakah terdapat pengaruh dari kedisiplinan siswa saat pembelajaran jarak jauh terhadap hasil belajar siswa kelas V sekolah dasar. penelitian ini merupakan penelitian kuantitatif dengan jenis penelitian ex post facto. Populasi berjumlah 95 orang yang merupakan siswa SD kelas V, teknik sampel yang digunakan merupakan teknik purposive sampling. Data yang dikumpulkan diperoleh dari hasil penyebaran instrumen penelitian berupa angket kedisiplinan siswa serta hasil studi dokumentasi siswa. Hasil dari penelitian ini menunjukan bahwa terdapat pengaruh yang positif dan signifikan antara kedisiplinan siswa saat PJJ (X) dengan hasil belajar siswa (Y), Berdasarkan nilai signifikansi, nilai Sig (2-tailed) sebesar 0,000 lebih kecil dari 0,05 ( 0,000 < 0,05) artinya bahwa Ho di tolak dan Ha diterima. dengan total pengaruh sebesar 18,5% yang tergolong memiliki pengaruh cukup berarti. Kata Kunci: Pembelajaran jarak jauh, Kedisiplinan siswa, Hasil belajar siswa ABSTRACT THE EFFECT OF STUDENT DISCIPLINE DURING DISTANCE LEARNING ON THE STUDENT LEARNING OUTCOME IN 5th GRADE ELEMENTARY SCHOOL (Ex Post Facto Research in Grade 5th Elementary School) By: Siti Maryam 1706103 This research is motivated by the problems faced during distance learning (PJJ), one of which occurs in the students themselves who are less disciplined. The purposes of this study are: 1) To determine the discipline of 5th grade elementary school students during PJJ, 2) To determine the learning outcomes of 5th grade elementary school students, 3) To find out whether there is an influence of student discipline during distance learning on the learning outcomes of first-class students. 5th elementary school. This research is a quantitative research with the type of ex post facto research. The population is 95 people who are elementary school students in class 5th, the sample technique used is purpose sampling technique. The data collected was obtained from the results of the distribution of research instruments in the form of student discipline questionnaires and the results of student documentation studies. The results of this study indicate that there is a positive and significant effect between student discipline during distance learning (X) and student learning outcomes (Y). Based on the significance value, the value of Sig (2-tailed) of 0.000 is smaller than 0.05 (0.000 < 0.05) means that Ho is rejected and Ha is accepted. With a total influence of 18.5% which is classified as having a significant influence. Keywords: distance learning, student discipline, student learning outcomes